Breaking the shackles: Zombie firms, weak banks and depressed restructuring in Europe - Dan Andrews; Filippos Petroulakis (European Central Bank (ECB), 2019)
This paper explores the connection between "zombie" firms (firms that would typically exit in a competitive market) and bank health and the consequences for aggregate productivity in 11 European countries. Controlling for cyclical effects, the results show that zombie firms are more likely to be connected to weak banks, suggesting that the zombie firm problem in Europe may at least partly stem from bank forbearance. The increasing survival of zombie firms congests markets and constrains the growth of more productive firms, to the detriment of aggregate productivity growth. Our results suggest that around one-third of the impact of zombie congestion on capital misallocation can be directly attributed to bank health and additional analysis suggests that this may partly be due to reduced availability of credit to healthy firms. Finally, improvements in bank health are more likely to be associated with a reduction in the prevalence of zombie firms in countries where insolvency regimes do not unduly inhibit corporate restructuring. Thus, leveraging the important complementarities between bank strengthening efforts and insolvency regime reform would contribute to breaking the shackles on potential growth in Europe.
Keywords: D24; G21; L25; O47; 330; Zombie Firms; Factor Reallocation; Productivity; Credit Constraints